Bagindo Dahlan Abdullah : Tokoh Nasional yang Terlupakan (1895-1950) - Idris Hamzah; Herman Herman; Ahmad Nurhuda (UIN Imam Bonjol Padang, 2022)
This article attempts to explain and reveal the historical experience of Baginda Dahlan Abdullah, a man from Pariaman, West Sumatra. The results discussed in this article are related to the biography and political struggles of Baginda Dahlan Abdullah between 1895 and 1950. Baginda Dahlan Abdullah was the son of Baginda Abdullah and Siti kali Tujuh (Uniang). He was born on July 5, 1895 in Kampung Parsir Pariaman. He is the eldest of 10 siblings. His education began with a Dutch school in Pariaman, then continued on to HIS in Padang, Kweek school For de Kock (Bukitinngi), then to the Netherlands. After attending a Dutch school, he finally attended Leiden University. His political career began in the Netherlands, he joined the